Communities of Practice: Developing IdentitiesofEmerging Scholars - Bridget A. Kriner; Karie A. Coffman; Anthony C. Adkisson; Paul G. Putman; Catherine H. Monaghan (Adult Education Research Conference, 2013)
Participating in a doctoral program can be a transforming experience shaping the learner’s identity. What learning spaces best facilitatesthis development? This roundtable presents findings of a study where a Community of Practice was used intentionallyto foster emerging scholars. We invite a discussion of others experience of becoming scholars.